Late Neoproterozoic to Early Palaeozoic palaeogeography of Avalonia: Some palaeomagnetic constraints from Nuneaton, central England - Vizan, Haroldo (2003)
Palaeomagnetic studies have been carried out on Neoproterozoic, Cambrian and Ordovician rocks in the Nuneaton inlier. England (52.5° N, 1.5° W). Three magnetic components were recognized, which provide a consistent structural and magnetic history of the inlier. Neoproterozoic volcaniclastic and intrusive rocks acquired a characteristic remanent magnetization (ChRM) dated at 603 Ma. Late Ordovician rocks are represented by lamprophyre and diorite intrusions and their ChRMs were probably imprinted during their emplacement, at about 442 Ma. The Lower Cambrian sedimentary sequence of the Hartshill Sandstone Formation, which unconformably overlies the Neoproterozoic rocks and hosts the Ordovician intrusions, does not preserve a primary magnetization but shows the imprints of the Late Ordovician (442 Ma) remagnetization, as well as a probable end-Carboniferous remagnetization. Palaeolatitudes calculated for the late Neoproterozoic rocks and Ordovician intrusions are in good agreement with other palaeolatitudes calculated for Avalonia during those times. Both the late Neoproterozoic and Late Ordovician rocks additionally show ChRMs with declination anomalies indicating a large tectonic rotation of the Nuneaton area, possibly during one of the Caledonian phases of deformation affecting southern Britain.